Population pharmacokinetics and dosing regimen design of milrinone in preterm infants. Issue 3 (11th May 2006) - Paradisis, Mary; Jiang, Xuemin; McLachlan, Andrew J; Evans, Nick; Kluckow, Martin; Osborn, David
Abstract : Aims: To define the pharmacokinetics of milrinone in very preterm infants and determine an optimal dose regimen to prevent low systemic blood flow in the first 12 h after birth. Methods: A prospective open-labelled, dose-escalation pharmacokinetic study was undertaken in two stages. In stage one, infants received milrinone at 0.25 μg/kg/min (n = 8) and 0.5 μg/kg/min (n = 11) infused from 3 to 24 h of age. Infants contributed 4–5 blood samples for concentration–time data which were analysed using a population modelling approach. A simulation study was used to explore the optimal dosing regimen to achieve target milrinone concentrations (180–300 ng/ml). This milrinone regimen was evaluated in stage two (n = 10). Results: Infants (n = 29) born before 29 weeks gestation were enrolled. Milrinone pharmacokinetics were described using a one-compartment model with first-order elimination rate, with a population mean clearance (CV%) of 35 ml/h (24%) and volume of distribution of 512 ml (21%) and estimated half-life of 10 h. The 0.25 and 0.5 μg/kg/min dosage regimens did not achieve optimal milrinone concentration-time profiles to prevent early low systemic blood flow. Simulation studies predicted a loading infusion (0.75 μg/kg/min for 3 h) followed by maintenance infusion (0.2 μg/kg/min until 18 h of age) would provide an optimal milrinone concentration profile. This was confirmed in stage two of the study. Conclusion: Population pharmacokinetic modelling in the preterm infant has established an optimal dose regimen for milrinone that increases the likelihood of achieving therapeutic aims and highlights the importance of pharmacokinetic studies in neonatal clinical pharmacology.